2006
DOI: 10.1159/000094281
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Sealants in Adolescents with High and Low Caries Experience

Abstract: The aim of this 3-year longitudinal study was to analyze caries increment and the caries-preventive effect of sealants in adolescents in the setting of the German national health system. 434 pupils (193 male, 241 female) took part in compulsory school examinations at age 12 (mean 12.3 ± 0.4 years) and 15 (mean 15.6 ± 0.3 years) according to WHO criteria, including the examination of sealants. Mean DMFT increased from 1.78 (± 2.15) to 3.97 (± 3.68), mean DMFS from 2.79 (±4.07) to 6.94 DMFS (± 8.34), respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
3
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 23 publications
0
17
3
7
Order By: Relevance
“…In contrast, low DMF-S values can be achieved with strict indications for sealants under the conditions that children follow a thorough preventive regime Christiansen, 2005, 2008]. The latter statement is supported in a risk-specific analysis from Germany performed by Heyduck et al [2006], who could show that sealants often failed if caries activity was not controlled with non-operative measures.…”
Section: Sealant Indication In Low Caries Prevalence Populationsmentioning
confidence: 99%
“…In contrast, low DMF-S values can be achieved with strict indications for sealants under the conditions that children follow a thorough preventive regime Christiansen, 2005, 2008]. The latter statement is supported in a risk-specific analysis from Germany performed by Heyduck et al [2006], who could show that sealants often failed if caries activity was not controlled with non-operative measures.…”
Section: Sealant Indication In Low Caries Prevalence Populationsmentioning
confidence: 99%
“…The results of studies assessing the effectiveness of fissure sealant according to patients' caries risk status have been contradictory 17,18) . Some studies have shown that fissure sealants are more effective if used in HR rather than low risk (LR) children 18,19) ; others have found that the higher the dft, the higher the risk of fissure sealant failure 20) , though such sealants are effective in individuals with low or moderate carious activity 21) . There has been no study discussing the preventive effect of Fuji VII in children of different caries risk status.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of over 3,000 Swedish adolescents, a social gradient was observed, with a higher caries increment reported among those residing in urban areas or who were children of immigrants or manual workers (6). Other studies have shown that the risk of developing new caries was most influenced by having had earlier experience of caries (5‐7). There has been only one report of New Zealand adolescents' dental caries experience over time; that was from the Dunedin Multidisciplinary Health and Development Study (DMHDS), where a caries increment of 2.2 surfaces from age 15 to 18 was observed two decades ago.…”
Section: Introductionmentioning
confidence: 99%